L’algherese - Caria, Marco; Autelli, Erica (Linguistik Online, 2025)
This article aims to give a portrayal of the linguistic features of Alghero – l’Alguer, the only Catalan-speaking town in Italy. In this paper the authors provide a description of the historical events that led to the catalanisation of the town, originally under the influence of the Ligurians, and consequently to the ethnolinguistic changes that characterise the territory of Alghero. After discussing the main aspects of the Catalan variety still spoken by the local population, special attention is given to the complex sociolinguistic scenario in which the minority language is increasingly lagging behind Italian. Finally, the efforts to protect Alghero’s linguistic heritage will be illustrated, also in the light of the most important initiatives led by the cultural associations.